2015
DOI: 10.1007/s00384-015-2421-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgical quality on prognosis in patients undergoing rectal carcinoma surgery after preoperative chemoradiation

Abstract: Even after preoperative chemoradiation, the surgical quality still has a strong impact on local control in patients with rectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Remarkably, despite this variety, results are comparable, in terms of technical and oncological quality, to other published series. 11,[29][30][31] For instance, anastomotic leakage rate represents a reliable technical surrogate marker for quality control, and Boyce et al 32 have reported a leakage rate of 12.9% following laparoscopic rectal resection with anastomoses below 6 cm. Indeed, a comparable leakage rate (12.1%) was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, despite this variety, results are comparable, in terms of technical and oncological quality, to other published series. 11,[29][30][31] For instance, anastomotic leakage rate represents a reliable technical surrogate marker for quality control, and Boyce et al 32 have reported a leakage rate of 12.9% following laparoscopic rectal resection with anastomoses below 6 cm. Indeed, a comparable leakage rate (12.1%) was also observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1). The 4 university centers, 4 referral centers, and 7 peripheral clinics contributed 104 (5-40), 152 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and 80 (1-33) patients, respectively. One hundred twelve patients were randomized to each treatment arm.…”
Section: Patient Population and Data Acquisitionmentioning
confidence: 99%
“…Nowadays, the completeness of the TME, and with that the quality of surgical tumor removal, may be expressed as the pathologic circumferential resection margin (pCRM). An intact and complete pCRM has been identified to lower local recurrence rates, whereas it may not impact on the development of distant metastases [17,18]. …”
Section: Current Surgical Treatment Strategies For Colorectal Cancermentioning
confidence: 99%
“…Leonard et al 18 found that patients who did not show downstaging after long-course chemoradiotherapy (CRT) had a higher incidence of MPR than patients who showed downstaging ( P = 0.0005). Kiehlmann et al 28 analyzed the prognosis of patients who underwent preoperative long-term CRT and TME and found that the 5-year LRR was 6.7% in patients with either an MRR or an IMR compared with the LRR of 50% in the patients with an MPR ( P = 0.015). Therefore, neoadjuvant radiotherapy could improve the local prognosis of patients planned to undergo resection.…”
Section: Prognostic Significance Of Mamementioning
confidence: 99%
“…However, even after neoadjuvant CRT, it should not be ignored that the quality (completeness) of the mesorectum still has a strong influence on local recurrence in patients with rectal carcinoma. 28 …”
Section: Prognostic Significance Of Mamementioning
confidence: 99%